Istishab Analysis of the Decision on Istbat Nikah as an Integrated Service of Mobile Session in Wanemana Religious Courts - Ismatul Maula; Siswanto; Ahmad Rezy Meidina; Musyafangah; Ubaidillah (Indonesian Academy of Social and Religious Research (IASRR), 2024)
Marriage in Indonesia is legalized by religion and the state. The state requires marriage registration or itsbat nikah for couples who have not registered with the relevant agencies authorized by the state. There are several considerations used by the judge in determining the decision, one of which uses the argument of istishab, so the formulation that interests the researcher is how the decision of the Wamena Religious Court Judge in itsbat nikah as an Integrated Service for the Mobile Session and how the istishab analysis in the decision of itsbat nikah as an integrated service for the Wamena Religious Court. The result of the research obtained is that the Itsbat Nikah at the Wamena Religious Court determines the granting of the application for istbat nikah in decision Number 5/Pdt.P/2021/PA.W with several considerations, including the Panel needs to put forward the Ulama doctrine as stated in the Book of Ushulul Fiqhi Abdul Wahab Khalaf that who knows that a woman is the wife of a man, it is punished that the husband and wife relationship remains as long as there is no evidence of the breakup of the marriage.